A natureza como sujeito de direitos?: as transformações do conceito de natureza e seu contexto de alienação no sudoeste do Pará, Brasil - CORRÊA, Simy de Almeida (Universidade Federal do Pará, 2018)
The main effort of the rescue work was the transformation of the concept of nature in Western philosophy and relate the history of law, analytic categories such as power and domination of drawing a particular way the crisis process environmental as discussed today. The aim was to discuss the role of law as a science and as an instrument of power that historically only led party on a dominant status and a mastery of the crisis experienced and propagated today. In this sense, it is inevitable question of the Amazon, in particular the state of Pará with record of deforestation and conflict. The reflection of all the transformations are experienced daily in the region where the nature diametrically opposed visions of the life of a conflict and therefore within the force field agents to show their power and dictate the future of this location. A brief analysis of how lawyers are manifested in processes related to large projects in the western region of Para to illustrate the vision and the nature of the concepts learned by these important agents. But what could be really different in this whole journey that repeats throughout the world? At the end, we present the latest discussions on the social empowerment of officers who resist the secular domination. Nature as a subject of rights is not only a thought or a biocentric theoretical aspect, is a decolonization movement of thought and theoretical constructs Europeanized / Western and a building accountability agents that give identity to place, the Amazon.